STRATIFIKASI SOSIAL DAN KETIMPANGAN DALAM OLAHRAGA - Fakhri Adam Angriawan Lubis; Efraim Christiando Karo Karo; Juhaina Fakhirah; Rahma Andesti Koto; Habibi Rahmat Gotama; Eka Kristian Sihotang; Yan Indra Siregar; Putra Arima (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Sport is often viewed as a social space that upholds the values of equality, sportsmanship, and equal opportunities for all members of society. However, in practice, the world of sport still exhibits significant social stratification and inequality. This study aims to analyze how social stratification affects individual access, participation, achievement, and opportunities in sport. The study employed a qualitative method with a literature review approach through analysis of various journals, books, and scholarly articles related to the sociology of sport. The results indicate that economic factors, education, gender, residential area, and social capital significantly influence a person's involvement in sport. Certain sports tend to be identified with specific social groups, creating indirect barriers for lower-class communities. Furthermore, unequal distribution of sports facilities also reinforces the inequality between urban and rural communities. This study confirms that sport is not entirely free from the influence of social structures. Therefore, more inclusive policies are needed to ensure equitable access to sport for all levels of society.